Exploring the validity and reliability of Active Motor Card: A Comprehensive Assessment of Gross Motor Development and Physical Fitness in Children Aged 6-9 Years - Taufik Taufik; Mashuri Eko Winarno; Imam Hariadi; Dona Sandy Yudasmara; Nurrul Riyad Fadhli (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research presents the Active Motor Card, an innovative evaluation instrument meticulously designed to comprehensively assess gross motor skills and physical fitness development in children aged 6-9 years. The study identifies the essential elements of motor development and physical fitness, highlighting the need for tailored assessments within this age group. The research delineates the process of development, encompassing an extensive review of existing literature, formulation of hypothetical tests, evaluation of content validity, empirical validation, and reliability assessment. The resultant Active Motor Card is validated by experts, thereby demonstrating its alignment with the target population's characteristics. Furthermore, the Gregory Analysis corroborates the appropriateness of each test item, indicating their level of difficulty or ease and their conformity with the expected characteristics of children aged 6-9. The reliability test, utilizing the Cronbach's alpha coefficient, affirms the consistency of the assessment. This product, designed for utilization in various settings, holds great potential as an effective instrument for monitoring children's motor skills and physical fitness, thereby making a positive contribution to the domains of physical education and sports. Further research is advisable to explore additional dimensions and enhance the assessment's validity, complexity, and representativeness across diverse populations.